Transforming Model to Meta Model for Knowledge Repository of Malay Intangible Culture Heritage of Malaysia - Radiah Amin (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Intangible Culture Heritage is very important as national treasure for a country since it is a part of identity of the country. Rapid technology changed and globalization is one of the reasons why new generation less interested to involve in culture heritage sector. Without any drastic action to safeguard Intangible Culture Heritage for the country it will cause endanger to disappearance. In this study researcher introduce a model of factors that contributing in archiving Intangible Culture Heritage. By transform from the model to meta model it will be a guidelines, standard and base for developing a repository of Intangible Culture Heritage. The finding for this research is a vital and very fruitful for intangible study and archiving and also as a main contribution for this study.DOI:http://dx.doi.org/10.11591/ijece.v2i2.205